2022
DOI: 10.1111/jdi.13818
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to healthy lifestyle behaviors as a preventable risk factor for severe hypoglycemia in people with type 2 diabetes: A longitudinal nationwide cohort study

Abstract: Aims/Introduction We investigated the associations between a combination of lifestyle factors and changes to these factors and the subsequent risk of severe hypoglycemia (SH) in type 2 diabetes patients. Materials and Methods Individuals with adult type 2 diabetes who underwent consecutive 2‐year interval health screening programs from 2009 to 2012 from the Korean National Health Insurance Service database were included and followed up until 2018. Information on history of smoking status, alcohol consumption a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Meanwhile, smoking, drinking, sleep patterns, and sedentary behavior were also significantly associated with various dimensions of a health-promoting lifestyle. Numerous studies have demonstrated that adopting healthy behaviors can prolong lifespan ( 5 ) and maintain overall health ( 50 ). In contrast, unhealthy behaviors, such as smoking, drinking, insufficient exercise, and inadequate sleep are significantly correlated with metabolic syndrome and can therefore impact health ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, smoking, drinking, sleep patterns, and sedentary behavior were also significantly associated with various dimensions of a health-promoting lifestyle. Numerous studies have demonstrated that adopting healthy behaviors can prolong lifespan ( 5 ) and maintain overall health ( 50 ). In contrast, unhealthy behaviors, such as smoking, drinking, insufficient exercise, and inadequate sleep are significantly correlated with metabolic syndrome and can therefore impact health ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that adopting healthy behaviors can prolong lifespan ( 5 ) and maintain overall health ( 50 ). In contrast, unhealthy behaviors, such as smoking, drinking, insufficient exercise, and inadequate sleep are significantly correlated with metabolic syndrome and can therefore impact health ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current smokers and those with high-risk alcohol intake were approximately half of the older DM population. However, 20% of older men are still current smokers and heavy alcohol drinkers; therefore, reinforcement education and intensive lifestyle modification should be emphasized, especially in older men with DM [ 29 ].…”
Section: Discussionmentioning
confidence: 99%